Effects of exercise modalities on physical function and quality of life in patients with heart failure: A systematic review and network meta‐analysis - Jiang‐Ying Li; Lu Chen; Qiu‐Chen Wang; Jian Zhu; Zhen‐Qing Ren; Li‐Chun Wang (ESC Heart Failure)
Abstract Aims This study aimed to evaluate the effects of various exercise modalities on physical function and quality of life in individuals with heart failure and to identify the most effective approaches. Methods and results A network meta‐analysis was conducted by searching PubMed, Embase and the Cochrane Library databases. Random‐effects meta‐analyses were performed to estimate mean differences (MD) and 95% confidence intervals (CI). A total of 60 randomized controlled trials, comprising 3261 participants, were included in the analysis. Yoga was associated with the greatest improvement in left ventricular ejection fraction (P‐score = 0.91, MD: 0.90; 95% CI: 0.42 to 1.38) and the most significant reduction in serum natriuretic peptide levels (P‐score = 0.965, MD: −1.46; 95% CI: −1.88 to −1.04). Interval training demonstrated superior effectiveness in increasing the 6‐min walk distance (6MWD) (P‐score = 0.873, MD: 113.01; 95% CI: 28.55 to 197.47). Combined aerobic and resistance training (AT + RT) showed the greatest benefits in enhancing peak oxygen uptake (VO2peak) (P‐score = 0.829, MD: 3.68; 95% CI: 2.23 to 5.13). High‐intensity interval training combined with inspiratory muscle training (HIIT + IMT) yielded the most significant improvements in quality of life (P‐score = 0.871, MD: −19.28; 95% CI: −26.42 to −12.14) and the greatest reduction in dyspnea (P‐score = 0.804, MD: −1.58; 95% CI: −2.64 to −0.52). Conclusions Current evidence suggests that yoga, interval training, AT + RT, and HIIT + IMT significantly enhance physical function and quality of life in individuals with heart failure, with each modality exhibiting distinct advantages. Further high‐quality studies are warranted to confirm these findings and refine exercise prescriptions for this population.